ANALISIS PENGARUH COUNTRY OF ORIGIN DAN EVENT SPONSORSHIP PEMILIHAN PUTERI INDONESIA TERHADAP BRAND AWARENESS DAMPAKNYA PADA KEPUTUSAN PEMBELIAN (Studi Pada Keputusan Pembelian Kosmetik Mustika Ratu di Kota Semarang) - Nusantari, Maulidya Permata; Idris, Idris (Diponegoro Journal of Management, 2017)
Nowdays, make up is not only use for someone who attending a formal event or a party. A change of desire become a necessity is an opportunity for manufacturers of cosmetic industry to develop its business.  The  purpose  of  this research  is  to  know  the  impact  of  country  of  origin  , event sponsorship,  and  brand  awareness  toward  consumer purchase  decision  on  buying  cosmetic products.  The sample used for this research is consumen who site in Semarang that had minimum one-time purchase Mustika Ratu’s products and watch Ajang Pemilihan Puteri Indonesia. The analysis technique used for this research is structural equation models with 22,0 AMOS program. The result of this research indicate that country of origin (0,297) and event sponsorship (0,642) have a positive and significant impact toward brand awareness. Country of origin (0,159), event sponsorship (0,347) and brand awareness (0,323) have positive and significant impact toward purchase decision.